Ethno Medicinal Survey of Plants with Anticancer Activities in Lapai, Agaie and Bida, Niger State, Nigeria - Yahaya, I (Enhanced Knowledge in Sciences and Technology, 2022)
Ethno-botanical survey of plants used in the management of cancer related ailments was conducted in selected areas of Agaie, bida and Lapai towns respectively. The continuous rise in cancer morbidity and death, as well as high cost and sde effects of the cancer therapies in use today, necessitates the need for the discovery of new and safe anticancer agents. Herbalists, herb sellers and traditional medicine practitioners (TMPs) living within the area of study were interviewed using a semi structured questionnaire. Snowball method was used to seek for respondents. Thirty two different species of plants were descovered to be used in treating cancer. Noticeable among these are Neem Tree, Pawpaw, Coconut, Moringa, Baobab leaves, Lime, Locust bean tree, Castor and Jatropha which are from the members of Fabaceae, Maliaceae, Moringaceae and Rutaceae family and were noticed to be very efficient and useful in the treatment of the disease based on their frequency of occurrence in the recipes. The plant part mostly used by the locals are the Leaves, roots, Fruits, bark, bulb, seeds and Rhizome. Common modes of administration done by the locals of these communities are Chewing, Infusion, Concoction and Decoction. A need for more research based on the findings of this survey is indeed very essential and recommended which can lead to discovery of new cancer drugs as well as keeping ample records of indigenous ways of treating cancer for future reference especially in the study area and hence reduce pain, cost and sudden deaths.